Interpreting the self : autobiography in the Arabic literary tradition - Reynolds, Dwight Fletcher, 1956-; Brustad, Kristen (University of California Press, 2001)
Autobiography is a literary genre which Western scholarship has ascribed mostly to Europe and the West. Countering this assessment and presenting many little-known texts, this comprehensive work demonstrates the existence of a flourishing tradition in Arabic autobiography.
Keywords: Arabic literature -- History and criticism.; Autobiography.; Authors, Arab -- Biography -- History and criticism.; Arabic literature -- Translations into English.; Autobiographies as Topic.; Littérature arabe -- Histoire et critique.; Autobiographie.; Écrivains arabes -- Biographies -- Histoire et critique.; autobiography (genre); 18.72 classical Arabic language and literature.; LITERARY CRITICISM -- African.; LITERARY CRITICISM -- General.; Arabic literature; Authors, Arab -- Biography; Autobiography; Arabisch; Autobiografie; Autobiografische Literatur; Geschichte; Literatur; Quelle; Aufsatzsammlung; Arabisch.; Autobiografieën.; autobiographies (literary works); Autobiographies; Criticism, interpretation, etc.; Translations; Autobiographies.